2015
DOI: 10.3748/wjg.v21.i35.10208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tumor necrosis factor-α antagonists on oxidative stress in patients with Crohn’s disease

Abstract: AIM:To investigate changes in oxidative stress in Crohn's disease (CD) before and after anti-tumor necrosis factor (TNF)-α treatment. METHODS:A total of 42 patients with active CD, who were scheduled to be treated by anti-TNF-α antibodies, were enrolled. Serum levels of diacron-reactive oxygen metabolites (d-ROM), biological antioxidant potential (BAP), and modified ratio of oxidative stress and antioxidant capacity (m-OA) were measured using the Free Radical Analytical System before and 8 wk after induction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In addition, two modifications to the BAP/dROMs ratio have emerged. First a proposal of Yamamoto et al (2015) called mOA that is an adjustment of the ratio by the constant 7.541 [114]: mOA=BAP/dROMs7.451.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, two modifications to the BAP/dROMs ratio have emerged. First a proposal of Yamamoto et al (2015) called mOA that is an adjustment of the ratio by the constant 7.541 [114]: mOA=BAP/dROMs7.451.…”
Section: Resultsmentioning
confidence: 99%
“…In both OSI, the oxidative part is the measurement of total peroxides or hydroperoxides, which are the oxidation products of several molecules, such as lipids, proteins, and amino acids; therefore, this is a measure of oxidative damage, what does not happen with the antioxidant capacity. The TAC and BAP have different principles, as well as their measurement units; both determinate the total nonenzymatic antioxidant capacity of biological samples, but although BAP is the most recommended procedures [125], the results of the different studies shown that this parameter almost does not change, making the index show no difference [114, 115, 122], especially when it is used to see the antioxidant potential (BAP/dROMs).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study that measured baseline protein levels of several cytokines in colon mucosa also found no differences [13]. Connection between anti-TNF loss of response and ROS response was also suggested in a post-treatment study of expression markers in colon [60]; however, measurements of the actual ROS in baseline serum of the NR and Re patients did not find any difference between the two groups [61]. It is possible that the “potential” differences in inflammation, cytokine and ROS responses between the NR and Re patients become relevant only after the therapy start.…”
Section: Discussionmentioning
confidence: 99%